Fetal aortic coarctation: A combination of third-trimester echocardiographic parameters to improve the prediction of postnatal outcome - Tuo, Giulia; Paladini, Dario; Marasini, Lucia; Buratti, Silvia; De Tonetti, Gabriele; Calevo, Maria G.; Marasini, Maurizio (Frontiers in Pediatrics, 2022)
Objectives This study aims to determine a combination of third-trimester echocardiographic parameters for improving the prenatal prediction of coarctation of the aorta (CoA) after birth. Methods We included all cases of suspected CoA during fetal echocardiography performed in the second and/or third trimester of pregnancy at Gaslini Children's Hospital between January 2010 and December 2020. The last prenatal ultrasound evaluation was reviewed considering most of the echocardiographic criteria were already published for prenatal CoA diagnosis. Associated minor cardiac anomalies, such as a ventricular septal defect, persistent left superior vena cava (PLSCV), and redundant foramen ovale (FO) membrane, as well as postnatal outcomes, were reported. Initial perinatal management was defined based on the risk stratification of CoA during prenatal echocardiography. Neonates were divided into two groups depending on the presence or absence of CoA after birth. Results A total of 91 fetuses with CoA suspicion were selected, of which 27 (30%) were confirmed with CoA after birth and underwent surgical repair. All cardiac parameters except redundant FO membrane and PLSCV showed a significant correlation with CoA. Statistical analysis confirmed that cardiovascular disproportion with right predominance carries an increased risk for occurrence of CoA, especially if already evident during the ultrasound evaluation in the second trimester. Aortic valve (AV) z-score and distal transverse aortic arch (TAA) z-score resulted as the best predictors of CoA after birth. The best cutoff point for CoA discrimination with ROC analysis was an AV z-score of −1.25 and a distal TAA z-score of −0.37. A total of 46% of those without CoA were diagnosed with a cardiac defect, which was not diagnosed in utero, pulmonary hypertension, or a genetic syndrome. Conclusion The current criteria for diagnosing CoA in utero allow accurate diagnosis of most severe cases but the rate of false positives remains relatively high for milder cases. A combination of anatomic and functional echocardiographic parameters might be used in stratifying the risk of CoA. We proposed the AV and the TAA diameter z-scores as the best predictors of CoA after birth. In addition, neonates without CoA deserve proper monitoring at birth because prenatal evidence of a significant cardiovascular discrepancy between the right and left cardiac structures has an inherent risk for additional morbidity postnatally.